Analysis of Factors Influencing Economic Growth in West Java During The 2018-2023 Period - Sultan Syarief Qasim (Journal of Development Economic and Social Studies, 2025)
This study aims to analyse the factors that influence economic growth in West Java Province during the period 2018-2023. The independent variables used in this study are investment, government spending, inflation, and the number of labour forces, with the dependent variable being economic growth measured using Gross Domestic Regional Product (GDRP). The model used in this study is the Random Effect Model (REM) based on the results of the Hausman and Lagrange Multiplier tests. The results showed that government spending and the size of the labour force had a positive and significant effect on economic growth, while investment and inflation had no significant effect. The findings suggest that increased government spending on infrastructure and public services as well as an increase in productively absorbed labour contribute to economic growth in West Java.